2008
DOI: 10.1155/2008/834153
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Counts and Platelet Activation Markers in Obese Subjects

Abstract: Objective. In this work we studied the correlation between platelet count, platelet activation, and systemic inflammation in overweight, obese, and morbidly obese individuals. Methods and subjects. A total of 6319 individuals participated in the study. Complete blood counts, high sensitivity C-reactive protein (hs-CRP) serum levels, and body mass index (BMI) were measured during routine checkups. Platelet activation markers were studied among 30 obese (BMI = 41 ± 8 kg/m2) and 35 nonobese (BMI = 24 ± 3 kg/m2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
94
1
11

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(118 citation statements)
references
References 31 publications
12
94
1
11
Order By: Relevance
“…Studies have found that, there is some sort of association between the increased number of immune cells and obesity as a result of a chronic inflammatory condition which is created by an increase in the production of cytokines by adipose tissue. It has also been show that obesity is associated with low-grade subclinical and smoldering inflammation [18,19]. The health effects of low-grade systemic inflammation in healthy adults have shown an increased risk of cardiovascular disease and diabetes mellitus [20].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that, there is some sort of association between the increased number of immune cells and obesity as a result of a chronic inflammatory condition which is created by an increase in the production of cytokines by adipose tissue. It has also been show that obesity is associated with low-grade subclinical and smoldering inflammation [18,19]. The health effects of low-grade systemic inflammation in healthy adults have shown an increased risk of cardiovascular disease and diabetes mellitus [20].…”
Section: Discussionmentioning
confidence: 99%
“…Positive associations between BMI and NLR were observed in two nonpatient populations [8,9], but a third study did not find BMI to be related to NLR nor to PLR [19]. With respect to their subcomponents, larger waist circumference has been related to higher levels of lymphocytes, neutrophils and platelets [20], and these cell counts were also increased in obese women compared with nonobese women [21,22]. Smoking has also been related to increased NLR in two studies in the general population [8,23] and to increased neutrophil [23] and lymphocyte counts [24].…”
mentioning
confidence: 99%
“…receptors; megakaryocytopoiesis; thrombocytopoiesis; hematopoiesis; microarray MEGAKARYOCYTOPOIESIS INVOLVES the proliferation and differentiation of hematopoietic stem cells to form megakaryocyte (MK) progenitors that undergo a maturation process that culminates in a release of ϳ10 11 platelets per day into the blood circulation (31). This process is tightly regulated by a number of factors, which include extracellular cues such as cytokines, cell-to-cell interactions, and cell-to-extracellular matrix interactions.…”
mentioning
confidence: 99%
“…Among cytokines that are known to act as important extracellular regulators of megakaryocytopoiesis is the main physiological stimulator of this specific cell-lineage commitment, thrombopoietin (TPO) (17). Additionally, interleukin 3 (IL3), interleukin 6 (IL6), interleukin 11 (IL11), stem cell factor (SCF), and fms-like tyrosine kinase 3 ligand act as positive regulators of MK development (17,31). There are also several cytokines such as transforming growth factor-beta (TGF-␤), platelet factor 4, and interleukin 4 (IL4) that are documented as negative regulators of MK development (31).…”
mentioning
confidence: 99%